ASSESSMENT OF SPECIAL PHYSICAL PREPAREDNESS OF GYMNASTS 13-15 YEARS OLD - Umarov, Khurshid (Журнал иностранных языков и лингвистики, 2022)
This article was presented, a variant of pedagogical control aimed at developing a system for evaluating the results of testing and creating integral indicators of physical fitness of 13-15 year old gymnasts is scientifically substantiated. It is shown that the proposed method of evaluating special physical preparedness will allow you to effectively manage the training process, and the achievement of model values of motor training will ensure the readiness of young gymnasts to perform competitive exercises in all-around events.